Muistin paikat siirtokarjalaisissa kodeissa - Sireni, Maarit (Suomen Maantieteellinen Seura, 2016)
After the Second World War, Finland had to cede part of its eastern territory to the Soviet Union. The population of this Karelian area, approximately 400 000 people, was evacuated and resettled in different parts of the newly defined Finnish territory. This article explores how descendants of the Karelian people visualize and materialize their original home places in the rural village where their grandparents and parents – who differed from the local population in terms of their native language, religion and cultural traditions – were resettled after the war. In particular, it examines the role of domestic material objects in remembering and producing re-memories of the lost places in ceded Karelia. The article draws on ethnographic research in the village of Rasimäki in Eastern Finland.